Quality of Life in Patient with Systemic Lupus Erythematosus (SLE) - Irma Yanih (Universitas Airlangga, 2016)
At present, the number of patients with Systemic Lupus Erythematosus (SLE) continues to increase every year. Treatment for patients with SLE is currently only useful to relieve or eliminate the symptoms that arise. This study aims to see a picture of the quality of life possessed by 13 SLE patients in terms of physical health, emotional health, self-image, pain, planning, fatigue, intimate relationships, and dependence on others. This research was carried out by designing a case study of 13 patients with SLE who reside in Surabaya and are members of the Surabaya branch of the Lupus Indonesia Foundation. Primary data were obtained from interviews with respondents with the help of the Lupus Quality of Life (LupusQoL) questionnaire and weight measurement with the help of digital weight scales. In this study there were 13 SLE patients with female sex between the ages of 15-40 years, highly educated with normal nutritional status, having a job, and earning IDR 1,740,000, had suffered from SLE> 5 years, and had good knowledge about Lupus and SLE. The quality of life of SLE patients shows good value in 3 aspects namely physical health, emotional health, and self-image. In the aspect of fatigue, pain, and dependence on others, there are still patients who have poor quality. The conclusion that can be drawn is that respondents who are majority sufferers of SLE have a fairly good quality of life except for the aspects of pain, fatigue, and dependence on others.